Antimicrobial and Antioxidant Activities of Various Freeze-Dried Yogurt Fermented with The Addition of Pineapple: An In Vitro Study - Auli, Winni Nur; Fajriani, Rahmatul; Anisah, Nadya; Lianti, Lita; Rahmadi, Isnaini; Nasution, Syahrizal (Pandawa Institute, 2025)
As a fermented milk, yogurt is functional food which contains a lot of bioactive compounds beneficial for human health. Yogurt can also be made with the addition of fruit such as pineapple, where pineapple contains phytochemical compounds as antimicrobial and antioxidant. This research aims to determine the antimicrobial and antioxidant activity of freeze-dried yogurt with raw material skim milk, full cream, and soy powder with addition of pineapple juice. Antimicrobial activity was conducted using disc diffusion and macro-dilution methods. While antioxidants activity conducted using the DPPH method at a maximum wavelength of 516 nm and FTIR method. The results showed that the antimicrobial activity of freeze-dried yogurt macro-dilution method against Escherichia coli showed that most yogurt at a concentration of 1 g/mL could be determined as minimum bactericidal concentration (MBC). Antioxidant activity showed pineapple soy yogurt has the lowest IC50 namely 43.67 ± 0.21 μg/mL. Functional group analysis of samples with the highest antioxidant activity in pineapple soy yogurt showed C–H, C–C, C=O, N–H, C=C, and amide II groups. The antimicrobial and antioxidant activities of freeze-dried yogurt are influenced by the raw materials used and the addition of pineapple fruit.